2015
DOI: 10.1007/s13197-015-1715-5
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and antioxidant properties of low molecular weight collagenous polypeptide (37 kDa) prepared from whale shark cartilage (Rhincodon typus)

Abstract: A low molecular weight type-II collagenous polypeptide (CIIp) from whale shark (WS) cartilage was prepared by thermolysin digestion; and examined for their physico-functional and antioxidant properties. The purified collagen was composed of an identical (α 1 ) 3 chains and was characterized as type-II. After hydrolysis with thermolysin, the α-chain of the WS collagen was degraded into smaller peptides with molecular weight ranging from 70 to 20KDa. CIIp was successfully separated from the hydrolysates with mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…Since the antioxidant properties of marine collagen peptides both from invertebrate and vertebrate sources have been well-documented in the last decade [36,42,50,51,52,53,54,55], we also decided to assess the radical scavenging activity of the four MCH fractions, both in cell-free and cellular in vitro tests to evaluate their potential as antioxidant drugs/supplements. In particular, for the cell-free measurements, two spectrophotometric tests were employed: the DPPH radical scavenging activity test for generic reactive oxygen species (ROS), and the Nitro Blue Tetrazolium (NBT)/riboflavin test measuring superoxide anion scavenging activity (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Since the antioxidant properties of marine collagen peptides both from invertebrate and vertebrate sources have been well-documented in the last decade [36,42,50,51,52,53,54,55], we also decided to assess the radical scavenging activity of the four MCH fractions, both in cell-free and cellular in vitro tests to evaluate their potential as antioxidant drugs/supplements. In particular, for the cell-free measurements, two spectrophotometric tests were employed: the DPPH radical scavenging activity test for generic reactive oxygen species (ROS), and the Nitro Blue Tetrazolium (NBT)/riboflavin test measuring superoxide anion scavenging activity (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Bovine collagen electrospun has been confirmed significant biocompatibility and no cytotoxicity. In continuation to our earlier research [23,24,25,26], in vivo wound healing properties of tilapia collagen sponges and bovine collagen electrospun were studied in rat models in order to evaluate its mechanism on accelerating wound healing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Proteases (pepsin, trypsin, and a‐chymotrypsin) and acid hydrolysis are simple and inexpensive methods to digest a protein into short‐chain peptides and free amino acids. Protein hydrolysates from many animals and plants, including fish collagen peptides (Kim et al, ), porcine myofibrillar protein (Saiga, Tanabe, & Nishimura, ), soy protein (Moure, Domínguez, & Parajó, ), acid‐soluble collagen and pepsin‐soluble collagen from the whale shark cartilage (Jeevithan, Bao et al, ) have been found to possess antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%